2006
DOI: 10.1534/genetics.106.062794
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Fungal Centromere H3 Proteins

Abstract: Centromere H3 proteins (CenH3's) are variants of histone H3 specialized for packaging centromere DNA. Unlike canonical H3, which is among the most conserved of eukaryotic proteins, CenH3's are rapidly evolving, raising questions about orthology and conservation of function across species. To gain insight on CenH3 evolution and function, a phylogenetic analysis was undertaken on CenH3 proteins drawn from a single, ancient lineage, the Fungi. Using maximum-likelihood methods, a credible phylogeny was derived for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 70 publications
2
27
0
Order By: Relevance
“…in those offering an opportunity for centromere drive (Melters et al, 2013). Similarly, adaptively evolving CenH3 has so far been detected only in lineages with asymmetric meiosis (Henikoff et al, 2001;Talbert et al, 2004Talbert et al, , 2008Hirsch et al, 2009;Schueler et al, 2010;Zedek and Bures, 2012;Finseth et al, 2015) and not in lineages displaying symmetric meiosis (Talbert et al, 2004(Talbert et al, , 2008Baker and Rogers, 2006), which is in accordance with the centromere drive model.…”
Section: Introductionsupporting
confidence: 56%
“…in those offering an opportunity for centromere drive (Melters et al, 2013). Similarly, adaptively evolving CenH3 has so far been detected only in lineages with asymmetric meiosis (Henikoff et al, 2001;Talbert et al, 2004Talbert et al, , 2008Hirsch et al, 2009;Schueler et al, 2010;Zedek and Bures, 2012;Finseth et al, 2015) and not in lineages displaying symmetric meiosis (Talbert et al, 2004(Talbert et al, , 2008Baker and Rogers, 2006), which is in accordance with the centromere drive model.…”
Section: Introductionsupporting
confidence: 56%
“…This has been shown for fungal CENH3's (Baker and Rogers 2006), but it is important to confirm this property for an organism with large tandem repeat centromeres that are likely specified epigenetically, rather than by sequence-specific DNA binding proteins. A previous study using plant tissue culture cells found that CENH3 from tobacco (Nicotiana tabacum) could localize to A. thaliana kinetochores when tagged at its C termini with GFP and expressed from the strong constitutive 35S promoter (Nagaki et al 2010).…”
Section: Discussionmentioning
confidence: 78%
“…Due to the small size of CDEII we were not able to accurately assess the extent of heterogeneity in polymorphism among centromeres on different chromosomes; more data from more isolates and centromeres would be useful in this regard. Interestingly, the two proteins directly interacting with CDEII, Cse4 and Mif2 (homologous to the fast-evolving mammalian CENPC protein), appear to be under strong purifying selection in yeast, with no indication of recurrent directional selection (Henikoff and Dalal 2005;Baker and Rogers 2006).…”
Section: Discussionmentioning
confidence: 99%